Minat Pemuda terhadap Pelestarian Seni Budaya Debus Banten - Mubarok, Ramadhani Al; Damanhuri, Damanhuri; Nida, Qotrun (Universitas Mathla'ul Anwar Banten, 2024)
Banten's cultural arts have unique characteristics that differentiate Banten from other regions. One of these cultural arts is Debus Banten. This art shows extraordinary human abilities and is not possessed by other humans. In its history, the Debus Banten Cultural Arts itself has experienced ups and downs. Judging from the researcher's experience as a Debus Banten Cultural Arts practitioner, this art is increasingly not popular among youth. This can be proven by the lack of young people practicing Debus Banten. The method used in this research is Qualitative Descriptive. Data was taken from Padepokan Ki Sinaba Mutiara Teluk Banten and the community or Youth who practiced or were at that location, using observation, interview and documentation techniques. The results of this research show that the level of public awareness, especially Youth, regarding the importance of preserving Banten's Debus Cultural Arts is very good. It's just that there are young people who are still reluctant to practice Debus Banten Cultural Arts for reasons of fear, difficulty, etc. The efforts made by the organization to preserve the Debus Banten Cultural Arts are sufficient. And the factors that influence the decline in Youth/I's interest in Debus Banten Cultural Arts are due to the development of the influence of Communication Media, Social Patterns, feelings of laziness, as well as the decline in Youth/I's interest in studying Debus Banten Cultural Arts.